In vitro Multiplication of Important Medicinal Plant Solanum nigrum L. - Ranjit Bansode; Vijay Kothekar, Narayan Pandhure*, (Recent Research in Science and Technology, 2010)
Abstract Medicinal plants are the most important source of life saving drugs for the majority of the world’s population. The biotechnological methods are important to select, multiply and conserve the critical genotypes of medicinal plants. In vitro regeneration holds tremendous potential for the production of high quality plant-based medicine. During the present investigations, direct multiple shoot formation Solanum nigrum L. in vitro was recorded with BAP 6 mg/lit and IAA 0.5 mg/lit. Maximum shoot emergence was achieved using nodal segment as explant with BAP 6 mg/lit. and IAA 0.5 mg/lit. The well developed shoots were sub cultured on a rooting medium containing IBA. Plants were multiplied in vitro and hardened successfully. Keywords: Solanum nigrum L. Multiplication, Micropropagation